Arab Countries in Transition : Economic Outlook and Key Challenges. (Policy Papers; Policy Paper, 2012)
Political uncertainty in the Arab Countries in Transition (ACT) has continued in recent months, especially as the escalation of the conflict in Syria is creating negative regional spillovers.1 While transition governments have maintained macroeconomic stability thus far, serious short-term risks continue, and the authorities have made limited progress in building consensus for needed economic reforms. With the exception of Libya, the ACTs' growth in 2012 has remained weak in light of continued policy uncertainty, regional tensions, the deteriorating global economy, and high food and fuel commodity prices. A moderate recovery is expected in 2013. The shrinking of fiscal and reserve buffers over the past year has left very little policy space and heightened vulnerabilities. Prompt policy action and timely and adequate international support are essential to maintain macroeconomic stability and address long-running structural deficiencies, to lay the foundation for inclusive growth and job creation for a young and growing population.